(x+1)²+(2x-3)²=(2x-4)²+(x-6)²
Răspunsuri la întrebare
Răspuns de
3
( x + 1 )² + ( 2x - 3 )² = ( 2x - 4 )² + ( x - 6 )²
( x + 1 )² = x² + 2x + 1
( 2x - 3 )² = 4x² - 12x + 9
( 2x - 4 )² = 4x² - 16x + 16
( x - 6 )² = x² - 12x + 36
x² + 2x + 1 + 4x² - 12x + 9 = 4x² - 16x + 16x + x² - 12x + 36
2x + 1 + 4x² - 12x + 9 = 4x² - 16x + 16 - 12x + 36
2x + 1 - 12x + 9 = - 16x + 16 - 12x + 36
2x + 1 + 9 = - 16x + 16 + 36
2x + 10 = - 16x + 16 + 36
2x + 10 = - 16x + 52
2x + 16x = 52 - 10
18x = 42
x = 42/18 simplificăm prin 6 ⇒ x = 7/3
Răspuns de
2
Alte întrebări interesante
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Biologie,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă